Peculiarities of growth and further productivity of purebred and crossbred cows - BashchenkoМ. І.; BoikoО. V.; HoncharО. F.; Sotnichenko, Y. M.; Lesyk, Y. V.; Iskra, R. Y.; Gutyj, B. V. (Regulatory Mechanisms in Biosystems, 2023)
Use of genetic specifics of pure breeding in animal husbandry allows cross breeders to produce herds that are completely of high breeding value, and also improve genetic potential of the best breeds. A relevant issue is determining the efficiency of crossbreeding of dairy breeds by analyzing the growth intensity of young bovine cattle, their reproductive ability and dairy productivity. We performed an analysis of experimental studies of using effective methods of selection, carried out a theoretical analysis, formulated hypotheses, used genealogical, biometrical and statistical methods, and assessed the productive properties of animals. We determined that the heifers from cross of the Ukrainian Red-Spotted cows with the sires of the Montbeliard breed – compared with the heifers from the Holstein bulls – had higher growth intensity and greater live weight during all the age periods. From birth until the age of one year, the Ukrainian Black-Spotted dairy heifers from the Holstein and Norwegian Red sires had no significant difference in weight. The heifers that resulted from cross of the Montbeliard and Ukrainian Red-Spotted dairy breeds had advantages over the purebred animals during all age periods, namely in the measurements of chest width, hook bone width, chest girth, ring metacarpal length. Body measurements of the replacement heifers, derived from the Norwegian Red and Holstein sires, varied within insignificant ranges depending on genotype, without significant difference. The animals were compact and proportionate; having received sufficient and complete diets, they had satisfactory weight categories. We determined that increase of the age of first insemination and first pregnancy was followed by decrease in the dairy productivity of cows. It ranged 0.021 to 0.064 in the bred heifers of different genotypes and breeds. There was observed an insignificant direct relationship between the abovementioned factors and the contents of fat and protein in milk. The shares of influence of age when the animals were first inseminated on milk yield accounted for 7.1% to 11.4%, 5.4–6.9 on fat content in milk, and 8.0–12.2% on protein fraction in milk. Crossbreeding can efficiently decrease the percentage of complicated deliveries and stillbirth rate, which in turn decreases the expenses for treatment of consequences of difficult calving, including the risk of decline in milk productivity and longer calving interval. However, there should be a careful approach to the selection of a breed, sire (preferably, its evaluation should be taken into account according to calving ease, especially when using the Montbeliard breed) and analysis of dams that are to be crossed with. Upgrading by mating to the Montbeliard and Norwegian breeds resulted in the crossbred cows that produced the greatest profit due to their heightened productivity. We should note that the estimated prices of extra products per cow give us grounds to state a positive effect from crossbreeding with the Montbeliard and Norwegian Red breeds. The performed studies confirm the benefits of identifying the efficiency of crossbreeding dairy breeds by an analysis of growth intensity of young bovine cattle.